2015
DOI: 10.1002/mrm.25862
|View full text |Cite
|
Sign up to set email alerts
|

On the accuracy of viscous and turbulent loss quantification in stenotic aortic flow using phase‐contrast MRI

Abstract: At spatial resolutions feasible in clinical three-dimensional PC-MRI measurements, viscous losses of stenotic flows are significantly underestimated, whereas TKE shows smaller errors and reduced sensitivity to spatial resolution. Magn Reson Med 76:191-196, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Our finding that 4D Flow MRI underestimates PLVS is consistent with previous studies21363738. In contrast to the PLVS, PRSS was overestimated with increased voxel sizes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding that 4D Flow MRI underestimates PLVS is consistent with previous studies21363738. In contrast to the PLVS, PRSS was overestimated with increased voxel sizes.…”
Section: Discussionsupporting
confidence: 92%
“…This is because Reynolds stress estimation from 4D Flow MRI assumes that the velocity distribution within the voxel is Gaussian2728. Strong velocity gradients within the voxel resulting from local acceleration of the flow or the flow separation can result in intravoxel velocity distributions that differ from a Gaussian distribution2738. The overestimation of intravoxel velocity standard deviation (IVSD) and TKE near the vessel wall or jet flow has been observed in previous studies3739.…”
Section: Discussionmentioning
confidence: 92%
“…Absolute quantification of flow and energy loss might be superior and more objective; furthermore, volumetric assessments might overcome limitatons of 2D analyses. However, validation using MRI, CFD, and particle image velocity data has only recently emerged, with mixed results relating to segmentation and resolution related errors 3536373839 . The computation of these parameters requires specialized algorithms and/or volumetric segmentations, neither of which were available for this study.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Viscous losses not related to turbulence also contribute to the total energy loss but have not been evaluated in this study. However, previous studies 19 showed that losses because of TKE exceeded nonturbulent viscous losses by a factor of 4 to 5 for moderate to severe stenosis, and currently used spatial resolutions are not sufficient for accurate viscous loss estimation.…”
Section: Study Limitationsmentioning
confidence: 94%
“…[14][15][16] Four-dimensional flow MRI also enables direct investigation of the mechanisms responsible for energy dissipation. 17,18 In particular, the assessment of turbulent kinetic energy (TKE)-the energy stored in turbulent flow-enables gauging energy losses caused by AS 19 because TKE is largely dissipated into heat. TKE can be quantified operator independently and reproducibly by 4D flow MRI, and it has been shown that TKE correlates with irreversible pressure loss as evidenced in a pilot study.…”
Section: Turbulent Kinetic Energy In Aortic Stenosismentioning
confidence: 99%